Evaluating the Effectiveness of E-Learning Implementation in the Professional Teacher Education Program through the CIPPO Model - Paat, Wensi R. L.; Katuuk, Deitje A.; Rawis, Joulanda A M; Lengkong, Jeffry Sony Junus; Umbase, Ruth (International Journal of Information Technology and Education, 2025)
This study aims to evaluate the implementation of e-learning in the Professional Teacher Education Program (PPG) at Manado State University using the CIPPO evaluation model, which consists of Context, Input, Process, Product, and Outcome components. The rapid transition to digital learning environments in higher education requires systematic evaluation to ensure the effectiveness and sustainability of e-learning practices, particularly in teacher professional development programs. A mixed-method approach was employed, involving quantitative surveys and qualitative interviews with PPG students, lecturers, and program administrators. Data were collected through structured questionnaires, observation, and document analysis. The findings indicate that the context component demonstrates strong institutional support and policy alignment, while the input component reveals adequate infrastructure but limited digital pedagogical competencies among some instructors. The process evaluation highlights the need for more interactive instructional strategies and consistent learning management system utilization. Product evaluation shows positive student performance and engagement, although variations exist across courses. Outcome analysis suggests that e-learning contributes to improved professional competence, digital literacy, and learning flexibility. The study concludes that the CIPPO model provides a comprehensive framework for assessing e-learning implementation and identifying areas for continuous improvement. Recommendations include strengthening lecturer training, enhancing technological infrastructure, and developing standardized e-learning guidelines to optimize the quality of PPG e-learning programs.